Foreword - Gurgu, Elena (Annals of Spiru Haret University. Economic Series, 2018)
According to the OECD Economic Outlook from the 21st of November 2018, the global expansion has peaked. Global GDP growth is projected to ease gradually from 3.7% in 2018, to around 3½ per cent in 2019 and 2020, broadly in line with underlying global potential output growth. In the near term, policy support and strong job growth continue to underpin domestic demand. However, macro-economic policies are projected to become less accommodative over time, and headwinds from trade tensions, tighter financial conditions and higher oil prices are set to continue.....